Determining the average inbreeding coefficient in two ways using the example of the Gyimesi Racka - Kárpáti, Edina; Gáspárdy, András; Sáfár, László; Gulyás, László (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
The Gyimesi Racka is one of the Zackel-group variants bred in Transylvania. In the early 1990s it was re-introduced into Hungary (only in small numbers), then in the following years the national population of the breed increased due to some major imports of breeding animals. The stud book herd of the Gyimesi Racka ewes consists of almost 1000 individuals today. The authors estimated individual Wright’s inbreeding coefficient (COI) using Pedigree Viewer software based on the whole pedigree data (from 2005 to 2020). Mean inbreeding coefficients were also determined at baseline and transformed values. The average COI of the total herd book population (n=16947) was 1.99%, compared to the higher value of the subpopulation of inbred individuals (n=3828, 8.81%). As the number of maternal generations increased, the COI increased too significantly (P
Keywords: coefficient of inbreeding; planning mating; descendance by maternal generations